2012
DOI: 10.1016/j.tine.2012.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The effects of handwriting experience on functional brain development in pre-literate children

Abstract: In an age of increasing technology, the possibility that typing on a keyboard will replace handwriting raises questions about the future usefulness of handwriting skills. Here we present evidence that brain activation during letter perception is influenced in different, important ways by previous handwriting of letters versus previous typing or tracing of those same letters. Preliterate, five-year old children printed, typed, or traced letters and shapes, then were shown images of these stimuli while undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
218
1
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(246 citation statements)
references
References 68 publications
14
218
1
13
Order By: Relevance
“…VMM provides a plausible cognitive pathway through which the motor aspects of handwriting can become more automated, reducing the cognitive load of the procedural aspects of this activity and freeing resources for the development of higher-order language skills [4]. This proposal is supported by the indirect effect of VMM on academic reading scores (through its relationship with academic writing scores) and is consistent with previous evidence of motor representations of letters reinforcing visual letter recognition in children [8][9][10].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…VMM provides a plausible cognitive pathway through which the motor aspects of handwriting can become more automated, reducing the cognitive load of the procedural aspects of this activity and freeing resources for the development of higher-order language skills [4]. This proposal is supported by the indirect effect of VMM on academic reading scores (through its relationship with academic writing scores) and is consistent with previous evidence of motor representations of letters reinforcing visual letter recognition in children [8][9][10].…”
Section: Discussionsupporting
confidence: 85%
“…Longcamp et al [8] found improvement for character recognition in 5-year-olds when they learnt the letters through copying compared with typing, whereas Naka [9] showed that repeated writing of Chinese or Arabic characters by Japanese primary school children led to increased recall compared with just looking at the characters. Most recently, brainimaging research has suggested that in pre-literate children the neural pathways associated with reading only activate in response to viewing letters if a child has previously been trained to print these letters free-form, as opposed to tracing their outline or typing them on a keyboard [10]. This implies that the activity of handwriting (and VMM) is advantageous for reading because it facilitates deeper knowledge of the component features that constitute a letter's form, aiding children's ability to distinguish and categorize letters.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that difficulty in automatic word identification is significantly associated with an EFL reader's ability to effectively comprehend what s/he is reading (Lyon, 1995;Torgersen, Reshot, & Alexander, 2001). The ability to recognize individual elements is crucial for reading (James & Engelhardt, 2012), and improves one's reading skills.…”
Section: Discussionmentioning
confidence: 99%
“…This issue is examined by James and Engelhardt (2012), whose study looks at how brain activity, when perceiving letters, is affected in different ways: either when the pupils have previously written the letter by hand (pencil); by using a keyboard on a computer, or when they recognise the same letter from among other letters on a sheet. They base their investigations on children (5 years old) and see that brain activity increases in central areas of the brain in a completely different way in those who have written the letter by hand than in those who have typed it on a keyboard or recognised it on a sheet.…”
Section: Literature Reviewmentioning
confidence: 99%